1996
DOI: 10.1210/mend.10.6.8776731
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CCAAT/enhancer-binding protein and nuclear factor-kappa B binding sites in interleukin-6 promoter inhibition by estrogens.

Abstract: Bone loss observed in postmenopausal women is clearly associated with a decrease in estrogen levels. Interleukin 6 (IL-6), a multifunctional cytokine involved in osteoclast differentiation, is secreted by osteoblasts and appears to be a key molecule in the osteoporotic process. As previous reports have shown that the human IL-6 promoter is inhibited by estradiol, we investigated the mechanism of estradiol (E2)-mediated IL-6 inhibition in human cells. Analysis of the IL-6 secretion as a function of time in oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…This apparent contradiction can be resolved if we assume that the contribution from the Ϫ225/Ϫ160 fragment involves synergistic interaction with NFB and that DHTs major effect is to inhibit this synergistic interaction. In fact, it has been demonstrated that NF-IL6, whose response element is located immediately adjacent to Ϫ160, synergizes with NFB to amplify the response mediated by the NFB site on the IL-6 promoter (56,57,77). This would be consistent with the observation that deletion of the Ϫ225/Ϫ160 fragment, which alters the context of the NF-IL6 site, results in marked diminution of the PMA-induction of the promoter.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This apparent contradiction can be resolved if we assume that the contribution from the Ϫ225/Ϫ160 fragment involves synergistic interaction with NFB and that DHTs major effect is to inhibit this synergistic interaction. In fact, it has been demonstrated that NF-IL6, whose response element is located immediately adjacent to Ϫ160, synergizes with NFB to amplify the response mediated by the NFB site on the IL-6 promoter (56,57,77). This would be consistent with the observation that deletion of the Ϫ225/Ϫ160 fragment, which alters the context of the NF-IL6 site, results in marked diminution of the PMA-induction of the promoter.…”
Section: Discussionsupporting
confidence: 75%
“…Several investigators have noted the NF-IL6 site is required for strong NFB-mediated induction of the IL-6 promoter (56,57). Therefore, when we delete the promoter to Ϫ160, which alters the region of the NF-IL6 response element, we lose the synergistic effect of NF-IL6 necessary for NFB-mediated activation of the IL-6 promoter.…”
Section: Il-6 Promotermentioning
confidence: 98%
“…The expression of cytokines IL-6 and TNFa is regulated directly by the upstream factor NF-jB [34][35][36][37]. LPS promotes the inflammatory response through the NF-jB pathway by activating phosphorylation of IjBa.…”
Section: Discussionmentioning
confidence: 99%
“…By mutation analysis, we showed that both C/EBP sites have a major contribution to the raloxifene inducibility of the IGF-I promoter. C/EBPs are transcriptional regulators that are highly expressed in liver and have previously been shown to be involved in ER-mediated promoter activation (31)(32)(33). C/EBP-␤ has been shown to be necessary for ER-␣ mediated down-regulation of the interleukin 6 promoter and to cooperate with a nuclear factor B site (32).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPs are transcriptional regulators that are highly expressed in liver and have previously been shown to be involved in ER-mediated promoter activation (31)(32)(33). C/EBP-␤ has been shown to be necessary for ER-␣ mediated down-regulation of the interleukin 6 promoter and to cooperate with a nuclear factor B site (32). Stein and Yang (31) demonstrated a direct in vitro interaction between a glutathione S-transferase-ER-␣ fusion protein and C/EBP␤.…”
Section: Discussionmentioning
confidence: 99%